Epidemiology of breast cancer in women in Norway - Pałac, Renata; Mielnik, Aneta; Cipora, Elżbieta (Journal of Education, Health and Sport, 2023)
Introduction. Breast cancer in women in Norway currently accounts for 23% of all cancer cases and is also the most common cause of death in this population. Thanks to the availability of preventive tests and the implementation of tests, many cases of the disease are diagnosed at an early stage, which has a positive impact on the prognosis. The introduction of new technologies and treatment methods in oncology has given many women a chance for longer survival and even complete recovery. The aim of the study was to present the epidemiological situation of women with breast cancer in Norway and to identify factors that may be important for the incidence, duration of survival and mortality due to this cancer. Material and methods. The work uses a review and analysis of the literature from the Norwegian online database Kreftregisteret Cancer in Norway (from 2019-2022) and a review of data published by: Norwegian Ministry of Health and Welfare and Statistics Norway. Results. Breast cancer in Norway is the most common cause of death in women under 65 years of age. In 2022, 4,197 new cases were recorded, i.e. more than in previous years, and the average age of women at diagnosis was 62 years. The incidence rate of breast cancer in the female population aged 50–69 was also higher and clearly associated with the more frequent use of hormonal treatment during menopause. The effects of treatment of this cancer in Norway are satisfactory, because nine out of ten women diagnosed with breast cancer survive 5 years after diagnosis. Conclusions. Breast cancer among women in Norway is still a serious health and social problem, but the functioning of the health care system and the attitude of women themselves allow for satisfactory treatment results. Evidence of significant progress in the diagnosis and treatment of women diagnosed with breast cancer is the fact that over 90% of patients with this cancer can be considered cured.